Analyzing Arabic-English interlanguage coda consonant clusters : optimality theoretic approach / Ala'a Mohammed Amin A Turkustani - Turkustani, Ala'a Mohammed Amin A (2011)
The study investigates the problematic English coda consonant clusters which Arabic speakers have in pronouncing English. This investigation involves a constraint-based analysis of interlanguage syllable structure within the optimality framework to see how the native language (NL) interferes in L2 pronunciation. The study presents an analysis of interlanguage (IL) syllable structure and answers a question in how NL interfere in Arabic speakers articulation of ESL syllable structure. It also investigates the effective role of the markedness of the forms in contributing to such difficulty in pronunciation. In other words, how these two factors affect Arabic speakers` pronunciation of English coda consonant clusters. This study focuses on the simplification of English codas by Arabic ESL learners and argues the interlanguage production within the OT framework to explain the origin and the choice of the simplification strategies used.